Modulation of expression and activity of ABC transporters by the phytoestrogen genistein: impact on drug disposition - Rigalli, Juan Pablo (Current medicinal chemistry, 2016)
ATP binding cassette (ABC) transporters are involved in drug absorption, distribution - and elimination. They also mediate multidrug resistance in cancer cel...